AKIBAT HUKUM TERHADAP PERJANJIAN GADAI YANG OBJEK GADAI BUKAN HAK MILIK DEBITUR (Studi Putusan Nomor 170/Pdt.G/2018/PN Skt) - Ningrum, Wulan Cahya; Rahmatiar, Yuniar; Abas, Muhamad (UNES Law Review, 2023)
A pawn agreement is an agreement between the creditor and the debtor, where the creditor obtains collateral for the goods provided by the debtor, and the debtor obtains collateral for the goods bound by him in the form of a money loan. The goods used as collateral or bound by a pawn agreement must be goods that belong to the debtor. The problem that can be discussed in this paper is the legal consequences of a pawn agreement with a pawn object that does not belong to the debtor as collateral and the judge's consideration in Decision Number 170/Pdt.G/2018/PN Skt. related to the object of pawn collateral. This paper uses normative juridical research methods. The conclusion of this research is that a pawn agreement held as collateral for a pawn object that does not belong to the debtor can make the pawn agreement null and void in accordance with Article 1320 of the Civil Code and analogous to the provisions of Article 1471 and the judge's consideration is correct and in accordance with applicable regulations. The verdict decided that The Joe An had legally committed a tort against PT Pegadaian and stated that the evidence which was also the object of the pawn collateral in this case must be returned to Koentjahjono Tanto as the owner of the gold shop.